Konsep Pendidikan Tauhid yang Terkandung Dalam Surat Al-Fatihah - Ahmad Darlis; Hadi Sufyan; Sri Rahmayani Manalu; Muhammad Amin; Asnil Aidah Ritonga (Jurnal Dirosah Islamiyah, 2023)
Islam is a religion that is rahmatan lilaa'lamin. Therefore, as a Muslim, it is obligatory to apply it and spread peace. The scholars have agreed that there is the knowledge that is obligatory 'ain, namely knowledge that is obligatory for everyone specifically for himself, and knowledge that is obligatory for kifayah if it is carried out by some people, then the obligation of others falls. The science that everyone must know is the science of monotheism which is related to the syahadatain, and beliefs about Allah swt. the almighty one who has no partners has no likeness to Him, has neither begotten nor begotten, and the belief that Allah swt. This research is a form of research (library research), namely research conducted using library sources, both from books and journals related to and supporting this research. The conclusions that can be drawn from the discussion above are first, monotheism education is a basic concept so that humans know human nature. Humans will obey Allah's commands and stay away from His prohibitions when humans have truly united Allah. This will be based on the actions of humans who always surrender to Allah for all aspects that humans want. Second, the purpose of monotheistic education in the discussion above emphasizes monotheism uluhiyyah, rububiyyah, and asma wa adjectives, and the realization of the content of monotheism. Third, the implication of monotheism education for educational institutions is that it is able to make humans conform to a number of things (holding fast to the values of monotheism, strong faith, and attachment to great obedience to Allah SWT and learning fundamentally). Keywords: Education, Interpretation, Theology